- Alasan Poligami Dan Persyaratan Izin Poligami Menurut Hukum Keluarga Islam Indonesia : - - Amanda Odelia; Khairani Bakri (Reformasi Hukum Trisakti, 2023)
Polygamy is a marital principle in which a man has 2 or more wives. Because marriage law in Indonesia adheres to the principle of monogamy, polygamy can be implemented if the polygamy requirements are met in Article 5 of the Marriage Law. The subject matter studied, what is the reason for polygamy according to Indonesian Family Law? The research method used in this writing is normative, the nature of the research is descriptive, the data used are secondary data by means of literature studies, qualitative data analysis, and deductive conclusions Article 4 Paragraph (2) of the Jo. Marriage Law Article 41 Letter a PP No. 9 of 1975 concerning the Implementation of the Jo. Marriage Law Article 57 of the Compilation of Islamic Law regulates the reasons for polygamy allowed in Indonesia. The rules regarding polygamy permit requirements are contained in Article 5 of the Jo. Marriage Law Article 55 and Article 58 of the Compilation of Islamic Law.  The conclusion of this study is that the reasons for polygamy and the conditions for polygamy permits are two things that must be met, in terms of applying for polygamy permits in accordance with existing laws and regulations. Verdict No. 5174/Pdt.G/2021/Pa.JT meets the requirements of polygamy permits. However, the judge did not consider the reasons for polygamy contained in Article 4 Paragraph 2 of the Marriage Law.